Automotive Aluminium Advancements: Driving Efficiency and Performance in Manufacturing - T.R. Vijayaram (International Journal of Manufacturing and Production Engineering, 2024)
Due to the special qualities of aluminum and its alloys, aluminum is one of the most versatile materials used in engineering and construction. Its electrical and thermal characteristics are good, and it reflects light and heat well. It is highly corrosion-resistant under many service conditions. Besides, it is soft, ductile and possesses lower specific gravity. It can be cast and worked into almost any form and can be given a wide variety of surface finishes. The need to improve performance and economy while adhering to strict environmental rules is driving a major revolution in the automobile sector. Aluminum has been a key component in this shift due to its natural recyclability and lightweight nature. The structure of pure aluminium is characterized by a relatively pure aluminium matrix. With all these outstanding properties, it has come to be of prime importance as engineering materials for various industrial applications. This review paper discusses the industrial applications of aluminium alloys.
Keywords: Aluminium alloys; Corrosion; Industrial application; Properties; vacuum forming